Pengaruh Workload, Spesialisasi Auditor, Rotasi Auditor, dan Komite Audit terhadap Kualitas Audit - Risti Fadhilah; Halmawati Halmawati (Universitas Negeri Padang, 2021)
Abstract: This research will explain and show the effect of workload, auditor specialization, auditor rotation, audit committee as an independent variable on audit quality which is the dependent variable in manufacturing companies listed on the Bursa Efek Indonesia from 2015 to 2019. This research is important to do because the slow growth of competent public accountants is an important matter that must be considered, given the growing growth of investment activities which has an impact on the increasing need for public accounting services. Seeing from various phenomena of audit failure due to not being an independent auditor and seeing from the point of view of failures based on violations of the code of ethics in the form of inadequate evidence collection so that it is related to the level of workload experienced requires further study. The results of the research and testing of the hypothesis conducted show that the first hypothesis is accepted where there is a significant negative effect between the workload and the quality of the audit results. The second hypothesis is accepted where there is a significant positive effect of auditor specialization on audit quality. The third hypothesis is rejected where there is no significant effect of audit rotation on the audit results. The fourth hypothesis is rejected, where there is no influence from the audit committee on the quality of the audit results.